TINGKAT PENGGUNAAN GENERATIVE AI DALAM PENYELESAIAN MASALAH MATEMATIKA PADA SISWA SMP DI KABUPATEN MAGETAN - Wanda Ani Nizar Auliya; Nagita Dyah Febrianti; Maraftul Afdilia; Nofa Fitri Oktavia; Arsyananda Rabbani; Rahma Zahyatul Ni'mah (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2026)
This study aims to analyze the level of Generative AI usage in assisting junior high school students in solving mathematics problems in Magetan Regency. The research employed a descriptive quantitative approach with a snowball sampling technique. Data were collected through an online questionnaire using Google Forms with a Likert scale. The participants consisted of 120 students from various grade levels. The results indicate that the level of Generative AI usage falls within the moderate to high category, with most students using it primarily to obtain quick answers. Some students also utilize AI to understand problem-solving steps and mathematical concepts. Students’ perceptions of Generative AI are generally positive, particularly in terms of time efficiency and ease of learning. However, several challenges were identified, including dependency on AI, potential inaccuracies in responses, and limited internet access. These findings suggest that Generative AI has significant potential as a learning support tool, but its use needs to be guided to promote conceptual understanding and critical thinking skills. Therefore, the role of teachers and appropriate educational policies is essential in effectively integrating this technology into mathematics learning.